Model of Inventory Planning Using Monte Carlo Simulation in Retail Supermarket with Consider To Competitors and Stimulus Strategies - Yuri Delano Regent Montororing; Murwan Widyantoro (Journal of Applied Engineering and Technological Science (JAETS), 2022)
Retail Supermarket is a retail company that provides various types of products to meet the primary needs of the community or people, such as food needs, various cleaning products, snacks, beverages, cosmetics, and many others. The growing retail business requires continously managed in retail company to work more effectively and efficiently in order to be able to face intense business competition so that business continuity can be maintained. The continuity of the company can be maintained if it is managed properly and has proper planning and control. Proper and careful planning followed by good control will continuously make the company's goal of achieving maximum profit achievable. This study will provide a proposal for inventory planning model using the Monte Carlo simulation method by paying attention to competitors and stimulus strategies, which can be used to predict sales for the next period so that the amount of inventory can be planned properly.